2007
DOI: 10.1007/s10680-006-9112-4
|View full text |Cite
|
Sign up to set email alerts
|

Choice and circumstance: Qualitative insights into contemporary childlessness in Australia

Abstract: Using data from in-depth interviews with 115 women, men and couples in eastern Australia for whom family formation was a recent, current or imminent future issue, this article explores contemporary childlessness among those physically able to have children. It differentiates between those childless by choice and by circumstance, and among other themes highlights (i) the role preservation of lifestyle appears to play as a motive for deliberate childlessness following development of a life course through early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 16 publications
(9 reference statements)
5
66
0
10
Order By: Relevance
“…The terms "childless by circumstance" or "social infertility" (which describe those who do not have a suitable partner, or who have a partner who does not want children) are used both in academic research (e.g., Carmichael and Whittaker 2007) and more generally (e.g., Black and Scull 2005;Day 2013). Indeed, while one member of a couple may be infertile or choose not to have children, for the other member this inability or unwillingness to have children may represent a circumstance which he or she has not chosen (Carmichael and Whittaker 2007). Several authors have suggested that there is a continuum of childlessness (Letherby 2002;McAllister and Clarke 2000).…”
Section: A Continuum Of Childlessnessmentioning
confidence: 99%
See 2 more Smart Citations
“…The terms "childless by circumstance" or "social infertility" (which describe those who do not have a suitable partner, or who have a partner who does not want children) are used both in academic research (e.g., Carmichael and Whittaker 2007) and more generally (e.g., Black and Scull 2005;Day 2013). Indeed, while one member of a couple may be infertile or choose not to have children, for the other member this inability or unwillingness to have children may represent a circumstance which he or she has not chosen (Carmichael and Whittaker 2007). Several authors have suggested that there is a continuum of childlessness (Letherby 2002;McAllister and Clarke 2000).…”
Section: A Continuum Of Childlessnessmentioning
confidence: 99%
“…Qualitative research has suggested that such women often feel they do not have an affinity for babies or young children. There is less support for the idea that these women are making their decision to remain childless to protect a high-powered career (McAllister and Clarke 2000;Carmichael and Whittaker 2007). At the other extreme are women who are childless due to a medical condition.…”
Section: A Continuum Of Childlessnessmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the women who feel very happy with their husband may fear about the negative effect of childbearing on their relationships. Some studies show the negative effect of childbearing on marital relationship quality [50]. Based on Friedman's, value of children, reinforcing family strength and reducing doubts are important factors influencing fertility decision making [51].…”
Section: Discussionmentioning
confidence: 99%
“…Muestran que la nomaternidad refleja una variedad de tendencias sociales en las que influyen: el acceso a la anticoncepción y al aborto, el incremento en los niveles de escolaridad y una mayor participación y oportunidad en el ámbito laboral (Blackstone, 2014;Gobbi, 2013;Keizer, Dykstra y Jansen, 2008;Carmichael y Whittaker, 2007;Koropeckyj-Cox y Pendell, 2007). Siendo el aspecto generacional un elemento importante, en tanto que, a pesar de la heterogeneidad de circunstancias y percepciones, los estudios señalan que las mujeres más jóvenes son quienes tienen mayores posibilidades de permanecer sin hijos a lo largo de su vida (Kelly, 2009;Gillespie, 2003).…”
Section: Entre La Norma Y La Práctica: La No-maternidadunclassified